Influence of company size, debt to equity ratio, current ratio, managerial ownership on earnings quality - Luahambowo , Nuryah Jasmine; Febriyanti, Diah (Central Research Institute for Agriculture (CeRIA), 2024)
This research aims to find out and analyze how company size, Debt to Equity Ratio, Current Ratio, and Managerial Ownership have developed on the Quality of Profits in Non-Cyclical Companies in the Food and Beverage Sub Sector listed on the Indonesia Stock Exchange in 2015-2022, and whether there is an influence The Influence of Company Size, Debt to Equity Ratio, Current Ratio, and Managerial Ownership on the Quality of Profits in Non-Cyclical Companies in the Food and Beverage Sub Sector listed on the Indonesia Stock Exchange 2015-2022, both partially and simultaneously. The research method used in this research is a quantitative research method with a descriptive and verification approach. The data used is secondary data. Data collection uses library research and documentation obtained from the official website of the Indonesian Stock Exchange. Sampling used a purposive sampling method and obtained a sample of 5 Non-Cyclicals Companies in the Food and Beverage Sub Sector listed on the Indonesian Stock Exchange. The data analysis techniques used in this research are the Classical Assumption Test, Multiple Linear Regression Test, Pearson Correlation Coefficient Test, Determination Coefficient Analysis, and Hypothesis Testing. The results obtained were that company size, Debt to Equity Ratio, Current Ratio, and Managerial Ownership simultaneously had no effect on Earnings Quality where Fcount < Ftable, namely 0.889 < 2.64. The coefficient value of determination of independent variable influence as much as 9.2% on Earnings Quality, this shows that another 90.8% influenced by other factors that are not used in this research.